Thoracic decompression point: New recommendation from ATLS 10 (Research, Society and Development, 2023)
The collection of liquid or gaseous fluids in the pleural cavity is a frequente occurence in thoracic trauma victims. The presence of content in space between parietal and visceral pleurae causes failure of the negative pressure needed for lung function, which induces lung tidal volume restriction and consequential acute breathing insufficiency for restrictive cause. Life-threatening thoracic injury can result from airway obstruction, tracheal bronchial tree injury, tension pneumothorax, open pneumothorax, massive hemothorax, and cardiac tamponade. Nevertheless, most of these injuries can be managed through relatively simple maneuvers such as airway control or chest decompression. However, subsequent editions of Advanced Trauma Life Support (ATLS) describe different approaches to the analyzed technique, in regard to the access to the thoracic cavity.  This study aims to present a bibliographic review concerning the technical and anatomical considerations used by American College of Surgeons (ACS) Committee on Trauma (COT) for the decision to change the surgical intervention in the chest decompression maneuver, as well as the analysis of the different techniques described in 2012, in the ninth ATLS edition, and 2018, the tenth and most recent protocol update.